EVEKTIFITAS BIMBINGAN PRA NIKAH BAGI CALON PENGANTIN SEBAGAI BEKAL MENUJU KELUARGA SAKINAH - Agripina Nurrahmayani Fradella (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research was motivated by the existence of government regulations, namely the regulation of the Director General of Islamic Community Guidance (BIMAS) of the Ministry of Religion Number 373 of 2017 which stipulates that prospective bride and groom couples who are going to get married are obliged to take part in marriage guidance. The purpose of this marriage guidance is as an effort by the government to maintain family resilience and minimize the occurrence of divorce. However, the facts on the ground are that there are still many divorces. Based on this background, the main issues are: 1) How effective is the pre-marital guidance implemented at the KUA Gudo District? 2) What is the influence of pre-marital guidance in creating a sakinah family carried out at the KUA Gudo District. This research is field research. This research was conducted at the KUA, Gudo District, Jombang Regency in January - February 2024. Primary data sources were taken from interviews with the head of the KUA, guidance facilitators and guidance participants. Secondary data sources are collected through legal sources, implementation documents, modules and other supporting data. Next, the data was analyzed using descriptive analysis. Based on the research that has been carried out, the researcher concluded firstly, the guidance carried out at KUA Gudo is in accordance with the technical instructions for marriage guidance, the implementation of the guidance can be said to be effective in terms of organizing activities and the provision of pre-facilities. The two marriage guidance carried out at KUA Gudo have a positive impact on the prospective bride and groom to build a sakinah family as seen from the increase in the prospective bride and groom's insight into the sakinah family.